2020
DOI: 10.1186/s13031-020-00321-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in humanitarian settings: documenting and sharing context-specific programmatic experiences

Abstract: Humanitarian organizations have developed innovative and context specific interventions in response to the COVID-19 pandemic as guidance has been normative in nature and most are not humanitarian specific. In April 2020, three universities developed a COVID-19 humanitarian-specific website (www.covid19humanitarian.com) to allow humanitarians from the field to upload their experiences or be interviewed by academics to share their creative responses adapted to their specific country challenges in a standardised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…COVID-19 also contributed to fear and wishes to return to home countries. Together, these findings suggest the importance of further exploring food insecurity and SGBV that may have worsened since COVID-19 across global contexts [3,4,35,36], specifically among refugee adolescents and youth in humanitarian settings to understand their lived experiences. Our findings also suggest the importance of psychosocial support for young refugees who may be experiencing fear, panic and social isolation during COVID-19 that may exacerbate pre-existing psychological distress [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 also contributed to fear and wishes to return to home countries. Together, these findings suggest the importance of further exploring food insecurity and SGBV that may have worsened since COVID-19 across global contexts [3,4,35,36], specifically among refugee adolescents and youth in humanitarian settings to understand their lived experiences. Our findings also suggest the importance of psychosocial support for young refugees who may be experiencing fear, panic and social isolation during COVID-19 that may exacerbate pre-existing psychological distress [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly salient to explore with refugees who may experience a high prevalence of psychological distress [34]. There are rising concerns of increased SGBV during COVID-19, including in humanitarian contexts [35,36]. Little is known of COVID-19-related stressors among refugee and displaced adolescents and youth, and how these may amplify pre-existing stressors.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the documentation of this programmatic adaptation is a novel contribution to the literature. A recent article by Singh et al (2020) reviewed programmatic adaptations and context specific interventions that are implemented by humanitarian organizations in response to the COVID-19 pandemic [40]. The review categorized these adaptations based on an operational framework that allows locating information by specific humanitarian activity, with one of these activities focusing on nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The review categorized these adaptations based on an operational framework that allows locating information by specific humanitarian activity, with one of these activities focusing on nutrition. The review indicated that few countries including Pakistan, South Sudan, Bangladesh have implemented nutrition program adaptations, but without providing any description of these adaptations [40]. A study by Francis and Pegg (2020) [41] in the humanitarian setting of the Niger Delta described an adaptation of the school nutrition program, and its transformation into socially distanced feeding programs, after the forced schools' closure amidst the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation